MENELAAH SIKAP TOLERANSI DALAM AKULTURASI SUKU DAN AGAMA PADA ARSITEKTUR MASJID MUHAMMAD CHENG HOO - Junaeny, Arini; Erma, Erma; Sani, Nur Fadhilah; Alrabani, Ahmad; Jusmirad, Muhammad (Bambuti, 2024)
Religious tolerance is an important aspect in Indonesian society which is diverse in ethnicity, ethnicity, and religion. The results of the Kompas R&D survey show that the majority of respondents consider Indonesian society to be quite tolerant, with 72.6% of respondents believing that tolerance is still maintained. This study focuses on the Muhammad Cheng Hoo Mosque in South Sulawesi, representing the acculturation of Chinese and Islamic culture in building architecture. The research shows that this mosque reflects tolerance and peace between ethnicities and religions. Ethnic and religious communities, including non-Muslims, welcome this mosque and consider it a symbol of harmony. This emphasizes the importance of tolerance and respect for other cultures and religions. Religious leaders see this mosque as strengthening inter-ethnic and religious relations. Ethnic and religious conflicts that have occurred in history have subsided with tolerance instilled in society. This confirms that religious tolerance is the key to creating harmony in a diverse society. The results of this research also underscore the importance of a qualitative approach in understanding cultural tolerance and acculturation in the context of multi-ethnic societies. This research provides insight into how communities can live together in harmony despite cultural and religious differences.